The dynamics of microbial community structure and metabolic function in different parts of cigar tobacco leaves during air-curing - Li, Wenlong; Yu, Jun; Li, Hao; Yang, Chunlei; Peng, Zheng; Zhang, Juan (Frontiers in Microbiology, 2024)
Air-curing is the initial step in the processing of cigar tobacco leaves. However, the dynamics of microbial community and metabolic functions in different parts of tobacco leaves during this process remain largely unclear. In this study, amplicon-based high-throughput sequencing revealed that Pseudomonas (9.0 to 29.9%) and Sphingomonas (0.5 to 13.8%) were the dominant bacterial genera in the early stages of air-curing, while Pantoea (1.7–90.4%) became predominant after air-curing. Microbial community diversity analysis indicated that species richness and diversity were significantly higher during the fresh leaf and withering periods. Functional prediction based on PICRUSt2 suggested that the microbial communities in the middle leaves exhibited higher abundances of metabolic pathways related to carbohydrates and amino acids than those in the upper leaves, potentially leading to the formation of more flavor compounds. The volatile flavor compounds were detected during the air-curing process by HS-SPME-GC–MS, with alkaloids and esters being the most prominent, although their accumulation periods differed across leaf parts. Furthermore, based on PLS-DA, 17 and 38 significantly changed flavor components were identified in the upper and middle leaves, respectively. Finally, the potential relationships between characteristic microbes and flavor components were explored based on Spearman correlation coefficient. It was found that multiple bacteria such as Rhodanobacter, Gemmatimonas, and Ramlibacter present in the middle leaves exhibited significant positive correlations with multiple flavor compounds such as 3,3-dimethylacrylic acid, phenylacetone, 2,3-butanedione, and geranylacetone, potentially promoting the flavor formation of cigar tobacco leaves during air-curing process. This study provides scientific insights into the role of microorganisms during the air-curing process of cigar tobacco leaves and offers a scientific basis for screening of specific functional microorganisms to improve and stabilize cigar tobacco flavor in the future.